Hepatitis B Virus-Related Glomerulonephritis: Not a Predominant Cause of Proteinuria in Korean Patients with Chronic Hepatitis B. (18th February 2015) - Yoo, Jeong-Ju; Lee, Jeong-Hoon; Yoon, Jung-Hwan; Lee, Minjong; Lee, Dong Hyeon; Cho, Yuri; Jang, Eun Sun; Cho, Eun Ju; Yu, Su Jong; Kim, Yoon Jun; Lee, Hyo-Suk
Abstract : Background/Aims . Hepatitis B virus (HBV) can form immune complexes which may result in various types of glomerulonephritis (GN). However, proteinuria can occur because of other kidney diseases besides HBV-related GN (HBV-GN). The aim of this study is to elucidate the causes of proteinuria and report on the clinical outcomes of HBV-GN. Methods . We reviewed the medical records of patients positive for serum hepatitis B surface antigen who underwent renal biopsies due to proteinuria at a tertiary medical center in Korea. Results . A total of 55 patients were included. HBV-GN was diagnosed in 20 (36.4%) of the patients by confirming the presence of immune complexes (12 of 13 membranoproliferative glomerulonephritis, 7 of 8 membranous glomerulonephritis, and 1 of 13 immunoglobulin A nephropathy). Twenty-one patients had other types of GN. A total of 13 (65%) HBV-GN patients were treated with antiviral agents for a median of 11 months. However, the degrees of proteinuria were not significantly reduced in the antiviral intervention group when compared to the control group. Conclusions . Proteinuria can be caused by various glomerular diseases and HBV-GN accounts for one-third of total GN cases. Well-designed prospective study is needed to assess whether antiviral therapy against HBV infection may improve the prognosis of HBV-GN.